2021
DOI: 10.21608/ejabf.2021.180680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioaccumulation and biosedimentation of some heavy metals on histological features in the cichlid fish, Tilapia zillii inhabiting Lake Qarun, Egypt.

Abstract: Lake Qarun constitutes one of the very important sectors in the Egyptian fisheries. It is a closed elongated marine lake with irregular shape (Figure 1). Lake Qarun contains different species of fish and is considered one of the most important wintering and nesting sites for many species of the migratory birds. It is approximately 55000 feddans (22000 hectares) or approximately 107 square kilometers (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This damage might be caused by the snails’ toxic biological system as a result of exposure to nanoparticles [ 66 ]. This result is similar to that of a study on the marine mollusk Mytilus sp., in which PCNA was assessed by qPCR and shown to be increased following exposure to nanoplastics [ 67 ]. Furthermore, the current findings agreed with those of [ 57 ], who found that PCNA was positively expressed, after the LC 25 treatment of the methanolic extract of N. oleander , in the ova, sperms, and digestive glands.…”
Section: Resultsmentioning
confidence: 99%
“…This damage might be caused by the snails’ toxic biological system as a result of exposure to nanoparticles [ 66 ]. This result is similar to that of a study on the marine mollusk Mytilus sp., in which PCNA was assessed by qPCR and shown to be increased following exposure to nanoplastics [ 67 ]. Furthermore, the current findings agreed with those of [ 57 ], who found that PCNA was positively expressed, after the LC 25 treatment of the methanolic extract of N. oleander , in the ova, sperms, and digestive glands.…”
Section: Resultsmentioning
confidence: 99%
“…Exposing snails to 44.15 mg/L of SeONPs caused great damage to gonadal cells; the connective tissue was deformed, the mature ova were destroyed, and the sperm were degenerated. These histopathological alterations might be related to the direct toxic effects of the heavy metals on the different organs of the target animals [ 59 ]. Similarly, Abdel-Tawab et al [ 16 ] reported severe damages in the digestive and hermaphrodite glands of B. alexandrina snails after exposure of to 314.5 mg/L of Cerium oxide nano-composite; furthermore, there were degeneration and rupture of sperms and ova.…”
Section: Discussionmentioning
confidence: 99%
“…These histopathological alterations might be related to the direct toxic effects of the heavy metals on the edible organs of target animals like fish (Elwasify et al 2021 ; Morad et al 2023 ), where the metal caused vacuolated hepatocytes, dilated central veins, compressed blood sinusoids, and congestion were seen in fish liver. Similarly, Abdel-Tawab et al ( 2022 ) reported that cerium oxide nanoparticles synthesized with Moringa oleifera seeds at a concentration of 314.5 mg/l caused great damages in both hermaphrodite and digestive glands.…”
Section: Discussionmentioning
confidence: 99%